ANALISIS HUBUNGAN DUTA WISATA DAN STRATEGI PROMOSI PADA DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN LEBAK DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI MASA PANDEMI - Risma Mardianah; Eris Harismasakti; Euis Ajizah (The Asia Pacific Journal Of Management Studies, 2023)
Tourism is a driving force for the economy that is proven to be able to contribute to the prosperity of the region and the country. The easiest way to observe the success of tourism is the increase in tourist arrivals from period to period. However, the Covid 19 pandemic that occurred resulted in a decrease in the number of tourist visits to Lebak Regency. due to government regulations related to preventing the spread of the Covid 19 virus pandemic. The purpose of this study was to determine the role of Tourism Ambassadors and Promotional Strategies at DISBUDPAR Lebak Regency before the pandemic and after or during the transition period of the Covid 19 pandemic. This study used qualitative research methods, with data analysis techniques according to Spradley. The results of this study are the differences in the role of tourism ambassadors and tourism promotion strategies before and after the pandemic or transition period. Where the role of tourism ambassadors is not only as a tourism promotion tool but also plays an active role in every activity outside tourism. Promotional strategies carried out before the pandemic were in the form of events and exhibitions as well as utilizing social media. After or during the pandemic transition, promotional strategies are carried out in a Hybrid manner by carrying out activities in the form of events, exhibitions and promotions with social media.